Celecoxib prevents curcumin‐induced apoptosis in a hematopoietic cancer cell model. Issue 10 (5th May 2014) - Sobolewski, Cyril; Muller, Florian; Cerella, Claudia; Dicato, Mario; Diederich, Marc
Abstract : Molecules targeting pro‐inflammatory pathways have demonstrated beneficial effects in cancer treatment. More recently, combination of natural and synthetic anti‐inflammatory drugs was suggested as an appealing strategy to inhibit tumor growth. Herein, we show that curcumin, a polyphenol from Curcuma longa and celecoxib induce apoptosis in hematopoietic cancer cell lines (Hel, Jurkat, K562, Raji, and U937). Further investigations on the most sensitive cell line, U937, indicated that these effects were tightly associated with an accumulation of the cells in S and G2/M for curcumin and in G0/G1 phase of cell cycle for celecoxib, respectively. The effect of celecoxib on cell cycle is associated with an induction of p27 and the down‐regulation of cyclin D1. However, in the case of combination experiments, the pretreatment of U937 cells with celecoxib at non‐apoptogenic concentrations counteracted curcumin‐induced apoptosis. We found that this effect correlated with the prevention of the accumulation in S and G2/M phase of cell cycle induced by curcumin. Similar results have been obtained when celecoxib and curcumin were co‐administrated at the same time. Overall our data suggest that this natural and synthetic drug combination is detrimental for cell death induction. © 2014 Wiley Periodicals, Inc.